Predictors and diagnosis of cardiac autonomic nervous dysfunction in patients with type 1 and type 2 diabetes mellitus - Kirill A. Popov (Endocrinology Research Centre, 2017)
Diabetic cardiovascular autonomic neuropathy (DCAN) is a diabetic complication characterised by early dissemination of sympathetic and parasympathetic, small-fibre neuronal degeneration. DCAN is the most dangerous and insidious complication that influences the clinical course and mortality rate of diabetes; however, it is often underestimated and not recognised by practitioners. Medical history and a physical examination are not sufficient for diagnosing DCAN. Laboratory diagnosis and the instrumental methods used to evaluate DCAN are time-consuming and not always available. Early detection of DCAN in diabetic patients is important for the early implementation of therapy. Today, there is no uniform diagnostic algorithm for DCAN in patients with various disorders of carbohydrate metabolism. This is due to the insufficient number of clinical trials and limitations of current protocols. This review presents an overview of the clinical and experimental studies of DCAN. The epidemiology, clinical manifestations, risk factors and underlying pathogenesis of DCAN are considered. The advantages and disadvantages of conventional and new diagnostic methods are discussed.